Investigating Factors Related to Situational Awareness in Hospital Operative Surgery Rooms|: A review study - Alireza Ghorpanpour; Saber Atari; Yousef Babayi Mesdaraghi (Shahid Sadoughi University of Medical Sciences, 2020)
Abstract Background: Awareness of the situation and condition of the patients is essential for medical personnel in order to avoid human errors. Various factors are associated with situational awareness in healthcare specialist, especially in surgical rooms. This review study examined the factors affecting the situational awareness of health staff. Research Method: All articles over situational awareness in the operating room conducted in 2010 to 2018 were collected and studied. To this end, the following databases were investigated: Scopus, ProQuest, Google scholar, Science Direct, PubMed, SID, Iran medex, Magiran, Medlib, and Civilica. To search these databases, the following key-words were used separately and in combination with each other: "situational awareness", "operating room","surgery","nurses","healthcare specialist","hospital staff".  Regarding the inclusion criteria, the articles which goals were matched with the criteria related to situational awareness in the operating room were selected. Results: Finally, 6 papers entered the study according to the selection criteria. The available documentation from 2013 to 2018 were compared in terms of method and outcome. Conclusion: The factors affecting situational awareness were education, sound factors, equipment, and individual characteristics. The effective factors that played an important role in the level of situational awareness of people who worked in the operating room were educating employees, using light music, using combined monitors, having physical movements during work, as well as using experienced staff in the operating rooms .